2016
DOI: 10.1007/978-3-319-45234-0_13
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Conceptual Model for the Relationship Between Social Media Behavior, Negative Consumer Emotions and Brand Disloyalty

Abstract: Companies have been facing the dark side of social media. Particularly, the odds of customer complaints and brand insults have increased tremendously. Social media has given a voice to disappointed consumers. They use the voice when they feel negative emotions, for example, due to product failures, service problems or unethical behavior. It seems reasonable to expect that the more ubiquitous social media becomes, the more it persuades people to share also their negative experiences. However, although social me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…Online, retaining, and satisfying consumers are the most vital factor that directly affects the organization. This research aligns with the existing literature (Jalonen and Jussila, 2016;Hechler and Kessler, 2018;Coetzee and Coetzee, 2019); when the retailer successfully fulfills its requirements, the consumer gets delighted repeating his choice to repurchase. On the other hand, if the online retailer fails to serve the consumer, the consumer regrets and, in extreme cases, becomes outraged about his decision.…”
Section: Value Consumer Emotionssupporting
confidence: 85%
See 1 more Smart Citation
“…Online, retaining, and satisfying consumers are the most vital factor that directly affects the organization. This research aligns with the existing literature (Jalonen and Jussila, 2016;Hechler and Kessler, 2018;Coetzee and Coetzee, 2019); when the retailer successfully fulfills its requirements, the consumer gets delighted repeating his choice to repurchase. On the other hand, if the online retailer fails to serve the consumer, the consumer regrets and, in extreme cases, becomes outraged about his decision.…”
Section: Value Consumer Emotionssupporting
confidence: 85%
“…When they feel betrayed, they tend to spread negative WOM (NWOM) as a response to their anxiety or anger. Jalonen and Jussila (2016) suggested that buyers who get dissatisfied with their selections get involved in negative e-WOM about that particular brand/company. Earlier research says that buyers suffering from failure to buy any product/services tend to participate actively and play a role in spreading NWOM due to the degree of regret after making bad choices.…”
Section: Consumer Regret and E-wommentioning
confidence: 99%
“…Gvili et al (2016) corroborates this finding by stating behaviour of consumers to word-of-mouth (WOM) is a significant antecedent of people's response to the eWOM. The level of influence eWOM has on switching intention is dependent on both consumer's behaviour towards the eWOM (Jalonen and Jussila, 2016) as well as the affect arising from the negative eWOM. Although the emotion appeal of negative eWOM is high due to the frustration, dissatisfaction and other negative emotions expressed by the sender, Wu and Wang (2011) support the notion that readers are likely to adopt the negative eWOM based on their individual agreement or disagreement with the negative eWOM.…”
Section: Discussionmentioning
confidence: 99%
“…Negative eWOM has strong impact on consumers' attitude towards a brand which in turn, influences brand switching behaviour, lowering consumer loyalty (Jalonen et al, 2016). This is attributed to the fact that negative eWOM are known to go viral thus, lead to greater influence on switching (Xiaoping, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Consumer switching is one of the main concerns of service providers [88], because negative WOM substantially impacts consumers' attitudes and influences switching behavior [89]. Switching intention represents the extent to which consumers are willing to switch from one company to another company [90].…”
Section: Effects Of Negative Wom On Switching Intention and Revision Intentionmentioning
confidence: 99%